Silicon negative electrode binder and battery pole piece prepared from same
By using Plulandosaccharide and polyacrylic acid as silicon negative electrode binders, the interaction with silicon particles is enhanced through multiple chemical bond cross-linking, solving the problem that traditional binders cannot provide sufficient conductivity and cope with volume changes, and significantly improving the cycling performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202510108626.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-22
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional non-conductive adhesives cannot provide sufficient electronic conductivity and are difficult to cope with changes in the volume of silicon particles, resulting in unstable electrode structure and affecting the cycle life and long-term stability of lithium-ion batteries.
Plulandosaccharide and polyacrylic acid with a mass ratio of a:10-a are used as binders to form a variety of chemical bond cross-linking effects with the hydroxyl group on the surface of silicon particles to enhance the interaction between the active material and the binder and improve the cycling performance of lithium-ion batteries.
The remaining capacity of lithium-ion batteries is achieved after 150 cycles of cycles, and the reversible specific capacity remains at 2187.2mAh/g, which significantly improves the cycling performance and structural stability of the battery.
Smart Images

Figure CN119859485A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of silicon negative electrode materials, and in particular to a silicon negative electrode binder and a battery pole piece prepared therefrom. Background Art
[0002] In the field of battery energy storage, innovation in negative electrode material technology is crucial to improving battery performance. In recent years, many cutting-edge battery technologies have emerged, injecting new impetus into the development of the new energy industry. Among them, silicon negative electrode has broad application prospects in high-capacity lithium-ion batteries (LIBs) because of its extremely high theoretical capacity of about 4200mAhg-1, low attenuation potential (<0.5Vvs.Li+ / Li), abundant reserves and environmentally friendly characteristics.
[0003] However, silicon will produce a huge volume change (about 300%) during the charge and discharge process, resulting in electrode structure damage and rapid capacity decay. This phenomenon leads to silicon particle rupture, electrolyte leakage and instability of the electrode-electrolyte interface, which seriously affects the battery's cycle life and charge and discharge efficiency. Therefore, how to optimize the structure and performance of silicon negative electrodes has become an important topic in current lithium battery research. Many researchers have effectively alleviated the volume effect by preparing nanoscale silicon particles through nanostructured design. Or silicon and carbon materials are compounded to form a core-shell structure or a uniformly mixed system, and the flexibility and conductivity of carbon materials are used to enhance the structural stability and electron transport capacity of the electrode. In many designs to improve the performance of silicon negative electrodes, binders play a vital role. It not only needs to effectively fix the active material on the current collector, but also needs to ensure the structural stability of the electrode. However, traditional non-conductive binders often cannot provide sufficient electronic conductivity, which limits the improvement of battery performance. At the same time, traditional linear binders are difficult to cope with the volume changes of silicon particles during the charge and discharge process of silicon negative electrodes, resulting in unstable electrode structures, thereby affecting the battery's cycle life and long-term stability. To address these challenges, developing powerful binder systems is a key strategy to improve the electrochemical performance of Si anodes. Summary of the invention
[0004] The purpose of the present application is to provide a silicon negative electrode binder and a battery pole piece prepared therefrom, based on the multiple chemical bond cross-linking effects between the binder and the hydroxyl groups on the surface of silicon particles, to enhance the interaction between the active material and the binder and improve the cycle performance of the lithium-ion battery.
[0005] To achieve the above-mentioned purpose, the present application provides a silicon negative electrode binder, which includes pullulan and polyacrylic acid in a mass ratio of a:10-a, wherein a is an integer.
[0006] The present application provides a battery pole piece prepared with a silicon negative electrode binder, comprising silicon powder, a binder, and a conductive agent in a mass ratio of 8:1:1 or 7:1:2; wherein the conductive agent is Super P; and the silicon powder is 60nm-2μm.
[0007] Preferably, the preparation process comprises the following steps:
[0008] Step 1: Fully stir and mix silicon powder, pullulan, polyacrylic acid and conductive agent with deionized water to form a slurry, and apply it on the copper foil; wherein the mass ratio of silicon powder, binder and conductive agent is 8:1:1 or 7:1:2;
[0009] Step 2: Transfer the copper foil to a vacuum oven for preheating, and then vacuum dry it to prepare a lithium-ion silicon negative electrode battery electrode material.
[0010] Preferably, in step 2, the preheating temperature is 80-150° C. and the preheating time is 1-5 h.
[0011] Preferably, in step 2, the preheating temperature is 120° C. and the preheating time is 3 hours.
[0012] Preferably, in step 2, the drying temperature is 60-120° C. and the drying time is 10-15 h.
[0013] Preferably, in step 2, the drying temperature is 80° C. and the drying time is 12 h.
[0014] Therefore, the present application provides a silicon negative electrode binder, which has the following beneficial effects:
[0015] 1. The present invention uses the biomacromolecule pullulan as a binder component, which has the characteristics of wide raw material sources, low cost, and green environmental protection. At the same time, the preparation method adopted is simple, does not require consumption of excess energy and equipment processing, is suitable for large-scale production, and has broad industrial application prospects.
[0016] 2. The present invention uses pullulan as a binder component. On the one hand, the surface of pullulan contains a large number of hydroxyl groups that form hydrogen bonds or van der Waals forces with the hydroxyl groups on the surface of silicon particles. The surface of pullulan contains a large number of carboxyl groups that interact with polyacrylic acid to chelate the hydroxyl groups on the surface of silicon particles to form covalent bonds. On the other hand, the cationic functional groups inside pullulan can carry ion flow in the electrolyte solution to form a conductive channel, so that the entire polymer has good conductivity. The prepared lithium-ion battery has a residual capacity of up to 76.3% after 150 cycles, and the reversible specific capacity remains at 2187.2 mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1Long cycle diagram (150 cycles) of a multifunctional chemically cross-linked silicon negative electrode material prepared in Example 1 at a current density of 0.2 A / g;
[0018] Figure 2 This is a rate performance diagram of a multifunctional chemically cross-linked silicon negative electrode material prepared in Example 1 at a current density of 0.2A / g-3.2A / g;
[0019] Figure 3 This is a mechanism diagram of this application. DETAILED DESCRIPTION
[0020] The technical solution of the present invention is further illustrated by the following embodiments.
[0021] Example 1
[0022] (1) 60 nm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:0.5:0.5:2 to form a slurry, which was then coated on a copper foil.
[0023] (2) The copper foil was transferred to a vacuum oven and preheated at 120°C for 3 hours, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0024] Example 2
[0025] (1) 100 nm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:0.5:0.5:2 to form a slurry, which was then coated on a copper foil.
[0026] (2) The copper foil was transferred to a vacuum oven and preheated at 120°C for 3 hours, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0027] Example 3
[0028] (1) 1 μm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:0.5:0.5:2 to form a slurry, which was then coated on a copper foil.
[0029] (2) The copper foil was transferred to a vacuum oven and preheated at 120°C for 3 hours, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0030] Example 4
[0031] (1) 2 μm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:0.5:0.5:2 to form a slurry, which was then coated on a copper foil.
[0032] (2) The copper foil was transferred to a vacuum oven and preheated at 120°C for 3 hours, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0033] Example 5
[0034] (1) 60 nm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:1:0:2 and stirred to form a slurry, which was then coated on a copper foil.
[0035] (2) The copper foil was transferred to a vacuum oven and preheated at 120°C for 3 hours, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0036] Example 6
[0037] (1) 60 nm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:0.9:0.1:2 to form a slurry, which was then coated on a copper foil.
[0038] (2) The copper foil was transferred to a vacuum oven and preheated at 120°C for 3 hours, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0039] Example 7
[0040] (1) 60 nm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:0.8:0.2:2 and stirred to form a slurry, which was then coated on a copper foil.
[0041] (2) The copper foil was transferred to a vacuum oven and preheated at 120°C for 3 hours, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0042] Example 7
[0043] (1) 60 nm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:0.7:0.3:2 to form a slurry, which was then coated on a copper foil.
[0044] (2) The copper foil was transferred to a vacuum oven and preheated at 120°C for 3 hours, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0045] Example 8
[0046] (1) 60 nm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:0.6:0.4:2 to form a slurry, which was then coated on a copper foil.
[0047] (2) The copper foil was transferred to a vacuum oven and preheated at 120°C for 3 hours, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0048] Example 9
[0049] (1) 60 nm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:0.4:0.6:2 to form a slurry, which was then coated on a copper foil.
[0050] (2) The copper foil was transferred to a vacuum oven and preheated at 120°C for 3 hours, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0051] Example 10
[0052] (1) 60 nm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:0.3:0.7:2 to form a slurry, which was then coated on a copper foil.
[0053] (2) The copper foil was transferred to a vacuum oven and preheated at 120°C for 3 hours, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0054] Embodiment 11
[0055] (1) 60 nm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:0.2:0.8:2 to form a slurry, which was then coated on a copper foil.
[0056] (2) The copper foil was transferred to a vacuum oven and preheated at 120°C for 3 hours, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0057] Example 12
[0058] (1) 60 nm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:0.1:0.9:2 to form a slurry, which was then coated on a copper foil.
[0059] (2) The copper foil was transferred to a vacuum oven and preheated at 120°C for 3 hours, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0060] Embodiment 13
[0061] (1) 60 nm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:0.5:0.5:2 to form a slurry, which was then coated on a copper foil.
[0062] (2) The copper foil was transferred to a vacuum oven and preheated at 80°C for 3 hours, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0063] Embodiment 14
[0064] (1) 60 nm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:0.5:0.5:2 to form a slurry, which was then coated on a copper foil.
[0065] (2) The copper foil was transferred to a vacuum oven and preheated at 150°C for 3 hours, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0066] Embodiment 15
[0067] (1) 60 nm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:0.5:0.5:2 to form a slurry, which was then coated on a copper foil.
[0068] (2) The copper foil was transferred to a vacuum oven and preheated at 120°C for 1 hour, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0069] Example 16
[0070] (1) 60 nm silicon powder, pullulan, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:0.5:0.5:2 to form a slurry, which was then coated on a copper foil.
[0071] (2) The copper foil was transferred to a vacuum oven and preheated at 120°C for 5 hours, and then the temperature was lowered to 80°C and vacuum dried for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0072] Comparative Example 1
[0073] (1) 60 nm silicon powder, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 8:1:1 and stirred to form a slurry, which was then coated on a copper foil.
[0074] (2) The copper foil was transferred to a vacuum oven at 80°C and dried under vacuum for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0075] Comparative Example 2
[0076] (1) 60 nm silicon powder, polyacrylic acid and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:1:2 and stirred to form a slurry, which was then coated on a copper foil.
[0077] (2) The copper foil was transferred to a vacuum oven at 80°C and dried under vacuum for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0078] Comparative Example 3
[0079] (1) 60 nm silicon powder, pullulan and conductive agent were mixed with an appropriate amount of deionized water in a ratio of 7:1:2 and stirred to form a slurry, which was then coated on a copper foil.
[0080] (2) The copper foil was transferred to a vacuum oven at 80°C and dried under vacuum for 12 hours to prepare the lithium-ion silicon negative electrode battery electrode material.
[0081] Application and performance testing
[0082] The silicon negative electrode material prepared in the above-mentioned embodiments and comparative examples is used as the negative electrode active material of lithium ion battery to prepare the pole piece (active material surface loading 0.8-1.5 mg / cm -2 ), and prepared sodium ion button batteries in a glove box, and tested the electrochemical properties of the button batteries.
[0083] Table 1 shows the performance test of lithium-ion batteries using pullulan as a silicon negative electrode binder component. The examples are compared with the comparative examples, indicating that the introduction of pullulan has a higher reversible capacity and first-week coulomb efficiency. This is because pullulan is a biological macromolecule with high viscosity characteristics. It contains a large amount of carboxylic acid (-COOH) and hydroxyl (-OH). By cross-linking with small molecules of polyacrylic acid, the binder has multiple functional groups such as hydroxyl and carboxyl, which enhances the bonding strength between the binder and silicon nanoparticles. The carboxyl group and the hydroxyl group on the surface of the silicon particles form a strong chemical bond through an esterification reaction, which enhances the structural stability of the material. Figure 1 , Example 1 at a current density of 0.2A / g, after 150 cycles, the residual capacity retention rate is as high as 76.3%, and still has a reversible capacity of 2187.2mAh / g; Figure 2 The rate performance shows that Example 1 has a reversible capacity of 1990.7 mAh / g at a current density of 3.2 A / g, which shows the excellent kinetic performance of Example 1 and proves the excellent performance of the silicon negative electrode material prepared by the present invention.
[0084] Table 1 Electrochemical performance of examples and comparative examples
[0085]
[0086]
[0087] Therefore, the present application provides a silicon negative electrode binder and a preparation method thereof, wherein pullulan is introduced into the binder so that it combines with multiple chemical bonds on the silicon surface to form a cross-linked structure, thereby improving the electrochemical performance of the silicon negative electrode.
[0088] In the description of this specification, the description with reference to the terms "an experimental example", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the experimental example or example are included in at least one experimental example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same experimental example or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more experimental examples or examples in a suitable manner.
[0089] Finally, it should be noted that the above experimental examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred experimental examples, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A silicon negative electrode binder, characterized in that: The binder comprises pullulan and polyacrylic acid in a mass ratio of a:10-a, wherein a is an integer.
2. The battery pole piece prepared by the silicon negative electrode binder according to claim 1, characterized in that: The invention comprises silicon powder, a binder and a conductive agent in a mass ratio of 8:1:1 or 7:1:2; wherein the conductive agent is Super P; and the silicon powder is 60nm-2μm.
3. The battery pole piece prepared by the silicon negative electrode binder according to claim 1, characterized in that: The preparation process includes the following steps: Step 1: fully stir and mix silicon powder, pullulan, polyacrylic acid and conductive agent with deionized water to form a slurry, and apply it on the copper foil; wherein the mass ratio of silicon powder, binder and conductive agent is 8:1:1 or 7:1:2; Step 2: Transfer the copper foil to a vacuum oven for preheating, and then vacuum dry it to prepare a lithium-ion silicon negative electrode battery electrode material.
4. The battery pole piece prepared by the silicon negative electrode binder according to claim 3, characterized in that: In step 2, the preheating temperature is 80-150° C. and the preheating time is 1-5 hours.
5. The battery pole piece prepared by the silicon negative electrode binder according to claim 3, characterized in that: In step 2, the preheating temperature is 120° C. and the preheating time is 3 h.
6. The battery pole piece prepared by the silicon negative electrode binder according to claim 3, characterized in that: In step 2, the drying temperature is 60-120° C. and the drying time is 10-15 hours.
7. The battery pole piece prepared by the silicon negative electrode binder according to claim 3, characterized in that: In step 2, the drying temperature is 80° C. and the drying time is 12 h.
Citation Information
Patent Citations
Preparation method of solid-state lithium ion battery
CN117996211A
Non-crosslinked / crosslinked polymer hybrid binder, preparation method therefor, and anode active material composition for lithium secondary battery including same
WO2015060483A1